Revolute-Cylindrical-Cylindrical-Cylindrical linkage optimum dimensional synthesis with static structural loading. (January 2019) - Lee, Wen-Tzong; Cosme, Jose; Russell, Kevin
General optimization models for the dimensional synthesis of defect-free Revolute-Cylindrical-Cylindrical-Cylindrical linkages with static loading are formulated and evaluated in this work. With these optimization models, Revolute-Cylindrical-Cylindrical-Cylindrical linkage dimensions required to approximate coupler positions or coupler path points while achieving static equilibrium (given coupler loads) within a maximum driver static torque are calculated. These models also include constraints that eliminate order, branch and circuit defects-defects that are common in traditional dyad-based dimensional synthesis. Therefore, the novelty of this work is the development of optimization models that permit the synthesis of order, branch and circuit defect-free Revolute-Cylindrical-Cylindrical-Cylindrical motion and path generators that also achieve static equilibrium within a maximum specified driver torque magnitude for specified coupler loads. This work conveys both the benefits and drawbacks realized when implementing these optimization models on a personal computer using the commercial mathematical analysis software package Matlab .